Correlation of joint roughness coefficient (JRC) and peak friction angles of discontinuities of Malaysian Schists - Abdul Ghani Rafek, Thian Lai Goh, . (2012)
The surface roughness of geological discontinuities plays an important role in influencing the stability of rock masses. Several approaches can be adopted for its determination. This paper presents a simple approach whereby two polynomial approximations have been derived to correlate the peak friction angle, f peak of discontinuity planes of fresh as well as slightly weathered schist bedrock with the Joint Roughness Coefficient, JRC